Light Absorption by Ambient Black and Brown Carbon and its Dependence on Black Carbon Coating State for Two California, USA, Cities in Winter and Summer. Issue 3 (1st February 2019) - Cappa, Christopher D.; Zhang, Xiaolu; Russell, Lynn M.; Collier, Sonya; Lee, Alex K. Y.; Chen, Chia‐Li; Betha, Raghu; Chen, Sijie; Liu, Jun; Price, Derek J.; Sanchez, Kevin J.; McMeeking, Gavin R.; et al.
Abstract: Observations from a wintertime and summertime field campaign are used to assess the relationship between black and brown carbon (BC and BrC, respectively) optical properties and particle composition and coating state. The wintertime campaign, in Fresno, CA, was impacted by primary emissions from residential wood burning, secondary organic and inorganic particle formation, and BC from motor vehicles. Two major types of BrC were observed in wintertime. One occurred primarily at night—the result of primary biomass burning emissions. The second was enhanced in daytime and strongly associated with particulate nitrate and the occurrence of fog. The biomass‐burning‐derived BrC absorbed more strongly than the nitrate‐associated BrC but had a weaker wavelength dependence. The wintertime BC‐specific mass absorption coefficient (MACBC ) exhibited limited dependence on the ensemble‐average coating‐to‐BC mass ratio ( R coat‐rBC ) at all wavelengths, even up to R coat‐rBC of ~5. For the summertime campaign, in Fontana, CA, BC dominated the light absorption, with negligible BrC contribution even after substantial photochemical processing. The summertime MACBC exhibited limited dependence on R coat‐rBC, even up to ratios of >10. Based on the four classes of BC‐containing particles identified by Lee et al. (2017, https://doi.org/10.5194/acp‐17‐15055‐2017 ) for the summertime measurements, the general lack of an absorption enhancement can be partly—although not entirely—attributed to an unequal distribution of coating materials between the BC‐containing particle types. These observations demonstrate that in relatively near‐source environments, even those impacted by strong secondary aerosol production, the ensemble‐average, mixing‐induced absorption enhancement for BC due to coatings can be quite small. Plain Language Summary: Particles in the atmosphere can scatter light, which has a cooling effect, or absorb light, which can contribute to localized atmospheric warming. Black carbon is a highly absorbing yet short‐lived climate pollutant that when coated with other materials can in theory have enhanced absorption. Organic compounds in particles can also absorb light, although tend to absorb less strongly than black carbon. Absorbing organic compounds are collectively referred to as brown carbon. We measured the composition and light absorption properties of atmospheric particles in wintertime Fresno, CA, and summertime Fontana, CA. In Fresno, we found two types of brown carbon contributed significantly to the overall light absorption by particles, in addition to absorption by black carbon. One of the brown carbon aerosol types in Fresno was emitted during wood burning, and the other was produced from chemical reactions in the atmosphere. In summertime Fontana, black carbon particles dominated the light absorption, with little contribution from brown carbon. Overall, at both sites the coating of materials onto black carbon particles had a limited impact on the absorption by black carbon, except to the extent that the materials themselves were absorbing. Key Points: Two co‐located types of ambient brown carbon were characterized, one from biomass combustion and one from secondary aerosol formation Limited mixing‐induced absorption enhancement observed in two distinct environments, despite substantial average coatings on black carbon